[Home Crushed Under Lava Rock on Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a house crushed under lava rock on Heimaey. The white house with a crushed, red roof sits to the right, surrounded by jagged, black rock. A grey stone wall sits in front of the house along green grass and white flowers at the bottom of the photograph. Groups of people stand ahead of the house or along the rocks. The side of a mountain is visible to the left against a grey, clouded sky.